Pengaruh Islamic Corporate Social Responsibility Terhadap Nilai Perusahaan: Studi Empiris pada Jakarta Islamic Index-70 - Sulfati, Andi (Insan Cita Bongaya Research Journal, 2022)
This study aims to examine the direct and indirect effects of corporate governance variables, profitability, on firm value through Islamic corporate social responsibility. The population used in this study are companies listed on the Jakarta Islamic Index-70 on the Indonesia Stock Exchange for the 2018-2020 period with a purposive sampling technique. The data analysis technique used Structural Equation Modeling (SEM) techniques, using AMOS 22 software. The results showed that ICSR had a positive effect on firm value. Profitability has a significant effect on ICSR. Corporate governance has no significant positive effect on ICSR. Profitability has no significant positive effect on firm value. Corporate governance has a negative effect on firm value. Profitability affects firm value mediated by ICSR. ICSR cannot mediate the relationship of corporate governance to firm value.